Theileria equi and Babesia caballi in horses in the Czech Republic - Bělková, Tereza; Bártová, Eva; Řičařová, Dagmar; Jahn, Petr; Jandová, Vendula; Modrý, David; Hrazdilová, Kristýna; Sedlák, Kamil (Acta tropica, 2021)
Theileria equi and Babesia caballi are protozoan agents causing equine piroplasmosis, endemic in countries all over the world. The aim of this study was to detect antibodies to T. equi and B. caballi in horses in the Czech Republic and to investigate the origin of the infection. Blood sera from 711 horses were examined with competitive enzyme-linked immunosorbent assay; positive samples were verified with indirect fluorescence immunoassay. Antibodies to T. equi and B. caballi were detected in eight (1.1%) and three (0.4%) horses, respectively. Infection with T. equi was confirmed by PCR and sequencing in the blood of five serologically positive horses. An autochthonous origin of T. equi infection could not be excluded in two (0.3%) horses. Intensive movement of horses across European countries and the expanding occurrence of competent tick vector Dermacentor reticulatus in the Czech Republic create an increasing risk of establishing active foci of equine piroplasmosis in the country.
Keywords: theilerióza; Babesia; nemoci koní; Hemoprotozoan parasites; Horses; Babesiosis; Theileriasis; Equine nuttaliosis; koně; zvířata; Dermacentor reticulatus; Theileria; Cattle; babezióza; Czech Republic; skot; Tick-born disease; Horse Diseases; Animals; Česká republika